Talempong Jao as a medium for cultural education and local wisdom preservation - Iswanto, Febri; Budiwirman, Budiwirman (Indonesian Research Journal in Education |IRJE|, 2026)
Traditional arts play an important role in preserving cultural heritage and transmitting educational values across generations. This study aimed to examine the cultural and artistic values of Talempong Jao and its contemporary existence in traditional wedding ceremonies in Air Panjang Village, East Panti Nagari, Pasaman Regency. This research used a qualitative descriptive approach, with observation, and semi-structured interviews to collect the data. Furthermore, the data were analyzed using data condensation, data display, and conclusion drawing, supported by source and method triangulation. The findings revealed that Talempong Jao embodies cultural values related to community identity, social cohesion, and cultural continuity, while promoting educational values such as cooperation, discipline, responsibility, and respect. However, its existence has declined due to the growing influence of modern entertainment and limited youth participation. This indicates that Talempong Jao functions as an informal educational medium that supports character development and cultural transmission. Integrating local cultural heritage into educational activities may contribute to cultural sustainability and strengthen local identity.